ANALISIS DAMPAK LINGKUNGAN KEGIATAN USAHA KATERING TERHADAP LINGKUNGAN PERMUKIMAN: STUDI KASUS EFATA CATERING DI KABUPATEN MIMIKA - Muhammad Akbar; Fitri; Bernabas Bane (Jurnal Ekonomi dan Bisnis, 2026)
The rapid growth of catering businesses has increased concerns regarding their potential environmental impacts, particularly related to waste generation, wastewater discharge, and air quality degradation. Catering activities that are not managed properly may contribute to environmental pollution and reduce environmental quality, especially in areas close to residential zones. Therefore, an environmental impact analysis is essential to ensure that catering operations are conducted in an environmentally responsible and sustainable manner. This study aims to analyze the environmental impacts arising from the operational activities of EFATA Catering, a food catering business located in Mimika Regency, Central Papua. The analysis focuses on identifying potential environmental impacts generated from food processing activities, the use of raw materials, packaging processes, and waste management practices. The study also examines the types and sources of waste produced, including solid waste, liquid waste, and food waste, which may affect the surrounding environmental quality. The research was conducted using an environmental impact analysis approach through field observations and qualitative descriptive analysis. The results indicate that EFATA Catering’s activities have the potential to cause environmental impacts, particularly on air quality, water quality, and soil conditions. However, these impacts are generally localized and manageable. Wastewater from washing activities, food residues, and cooking odors are the main sources of potential environmental disturbance. Furthermore, the study evaluates environmental management and monitoring efforts that can be implemented to minimize negative impacts while enhancing positive socio-economic contributions. The findings suggest that proper waste segregation, improved wastewater management, adequate kitchen ventilation, and routine environmental monitoring are essential to support environmentally friendly and sustainable catering operations. Overall, EFATA Catering is considered environmentally feasible to operate, provided that appropriate environmental management measures are consistently implemented